2020
DOI: 10.1155/2020/7104243
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Infusion of Autologous Adipose-Derived Regenerative Cells in Autoimmune Refractory Epilepsy: Evaluation of Safety and Efficacy

Abstract: Objective/Purpose. Evaluation of efficacy and safety of autologous adipose-derived regenerative cells (ADRCs) treatment in autoimmune refractory epilepsy. Patients. Six patients with proven or probable autoimmune refractory epilepsy (2 with Rasmussen encephalitis, 2 with antineuronal autoantibodies in serum, and 2 with possible FIRES) were included in the project with approval of the Bioethics Committee. Method. Intrathecal injection of autologous ADRC acquired through liposuction followed by enzymatic isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…Both in vitro and in vivo results indicated allogeneic ADSCs presented immune tolerance and could not stimulate lymphocyte proliferation, which allows the possibility of ADSCs xenotransplantation [ 73 ]. Preclinical studies and clinical trials have shown that ADSCs have a good therapeutic effect in various autoimmune diseases [ 74 – 76 ].…”
Section: Basic Functions Of Adscsmentioning
confidence: 99%
“…Both in vitro and in vivo results indicated allogeneic ADSCs presented immune tolerance and could not stimulate lymphocyte proliferation, which allows the possibility of ADSCs xenotransplantation [ 73 ]. Preclinical studies and clinical trials have shown that ADSCs have a good therapeutic effect in various autoimmune diseases [ 74 – 76 ].…”
Section: Basic Functions Of Adscsmentioning
confidence: 99%
“…Importantly, the stem cell transplantation was safe, exhibiting no adverse events ( DaCosta et al, 2018 ). In another clinical trial, autologous adipose-derived regenerative cells (ADRCs) were intrathecally administered via liposuction to autoimmune refractory epileptic patients ( Szczepanik et al, 2020 ). They received treatment three times for every three months ( Szczepanik et al, 2020 ).…”
Section: Recent Preclinical and Clinical Evidence Supporting The Safementioning
confidence: 99%
“…In another clinical trial, autologous adipose-derived regenerative cells (ADRCs) were intrathecally administered via liposuction to autoimmune refractory epileptic patients ( Szczepanik et al, 2020 ). They received treatment three times for every three months ( Szczepanik et al, 2020 ). The patients demonstrated cognitive recovery, as observed in ameliorated academic, social, and motor performance.…”
Section: Recent Preclinical and Clinical Evidence Supporting The Safementioning
confidence: 99%
See 2 more Smart Citations